2007
DOI: 10.1021/cb6003788
|View full text |Cite
|
Sign up to set email alerts
|

Selective Tumor Cell Targeting Using Low-Affinity, Multivalent Interactions

Abstract: This report highlights the advantages of low-affinity, multivalent interactions to recognize one cell type over another. Our goal was to devise a strategy to mediate selective killing of tumor cells, which are often distinguished from normal cells by their higher levels of particular cell surface receptors. To test whether multivalent interactions could lead to highly specific cell targeting, we used a chemically synthesized small-molecule ligand composed of two distinct motifs: (1) an Arg-Gly-Asp (RGD) peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
240
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(249 citation statements)
references
References 50 publications
6
240
0
Order By: Relevance
“…Mammen et al (9) recognized the importance of this type of system more than ten years ago. Since then, the concept of multivalency has found numerous applications in cell biology (7, 11), supramolecular chemistry (10), nano-medicine (4, 6), immunology (12, 13), and cancer treatment (2,3,5,14), to name but a few examples. The work of Davis et al There is a substantial body of theoretical work that aims to explain the pronounced enhancement in binding strength that certain multivalent systems can present in comparison with their monovalent counterparts (15-17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mammen et al (9) recognized the importance of this type of system more than ten years ago. Since then, the concept of multivalency has found numerous applications in cell biology (7, 11), supramolecular chemistry (10), nano-medicine (4, 6), immunology (12, 13), and cancer treatment (2,3,5,14), to name but a few examples. The work of Davis et al There is a substantial body of theoretical work that aims to explain the pronounced enhancement in binding strength that certain multivalent systems can present in comparison with their monovalent counterparts (15-17).…”
mentioning
confidence: 99%
“…Experiments indicate that such selective behavior can be obtained using multivalency (5)(6)(7)(8). During multivalent interactions a type of particle (henceforth referred to as the "guest") uses multiple ligands to bind simultaneously to several of the receptors displayed by another type of particle or surface (the "host") (9, 10).…”
mentioning
confidence: 99%
“…Such selectivity can be achieved by exploiting multivalency. A series of recent experimental and theoretical papers have shown that multivalent carriers (nanoparticles or polymers) can distinguish target surfaces (cells) on the basis of their receptor concentration, rather than just on the basis of the presence of a suitable receptor (5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…Here we have shown the functional advantage of covalent protein polymerization for capture of cells. Multivalency is a powerful way to enhance biological function and with the right ligand organization gives dramatic improvements in affinity, kinetics and specificity (42,43). The multivalency of the SpyLigase-assembled affibody polymers enhanced the capture of cancerous cells expressing low levels of tumor antigen, without loss of specificity.…”
Section: Discussionmentioning
confidence: 99%